Crested wheatgrass in grazed/ungrazed areas - Gunther, Deb, photographer (Colorado State University. Libraries, 2001)
Grazed and ungrazed pastures showing growth of crested wheatgrass in ungrazed area, on SGS.
Keywords: exclosures; SGS; plants; landscapes